Methods for Clearance Influence Analysis in Planar and Spatial Mechanisms - Venanzi, Stefano <1975> (Alma Mater Studiorum - Università di Bologna, 2004)
This doctoral dissertation presents a new method to asses the influence of clearancein the kinematic pairs on the configuration of planar and spatial mechanisms. The subject has been widely investigated in both past and present scientific literature, and is approached in different ways: a static/kinetostatic way, which looks for the clearance take-up due to the external loads on the mechanism; a probabilistic way, which expresses clearance-due displacements using probability density functions; a dynamic way, which evaluates dynamic effects like the actual forces in the pairs caused by impacts, or the consequent vibrations. This dissertation presents a new method to approach the problem of clearance. The problem is studied from a purely kinematic perspective. With reference to a given mechanism configuration, the pose (position and orientation) error of the mechanism link of interest is expressed as a vector function of the degrees of freedom introduced in each pair by clearance: the presence of clearance in a kinematic pair, in facts, causes the actual pair to have more degrees of freedom than the theoretical clearance-free one. The clearance-due degrees of freedom are bounded by the pair geometry. A proper modelling of clearance-affected pairs allows expressing such bounding through analytical functions. It is then possible to study the problem as a maximization problem, where a continuous function (the pose error of the link of interest) subject to some constraints (the analytical functions bounding clearance- due degrees of freedom) has to be maximize. Revolute, prismatic, cylindrical, and spherical clearance-affected pairs have been analytically modelled; with reference to mechanisms involving such pairs, the solution to the maximization problem has been obtained in a closed form. === L’attività di ricerca presentata nella tesi di dottorato concerne lo studio dell’influenza del gioco nelle coppie cinematiche in meccanismi piani e spaziali. Tale tema è stato spesso oggetto di studi, tanto nella letteratura scientifica passata quanto in quella attuale. Da uno studio approfondito, si possono dedurre diverse metodologie per affrontare il problema: metodologie di tipo statico/cinetostatico, che determinano la ripresa nel gioco nelle coppie a seguito dell’azione di un carico; metodologie di tipo probabilistico, che esprimono lo spostamento nelle coppie con gioco in termini di funzioni densità di probabilità; infine, metodologie che si interessano al problema dinamico, volte a determinare effetti quali le effettive forze nelle coppie, o gli urti successivi al distacco e le conseguenti vibrazioni. La tesi in oggetto presenta una nuova metodologia per affrontare il problema. Tale metodologia differisce dalle precedenti poichè presenta un’analisi di tipo puramente cinematico. Con riferimento ad una configurazione assegnata per un meccanismo, l’errore di posizione del membro di riferimento viene espresso come funzione vettoriale dei gradi di libertà introdotti dal gioco. La presenza di gioco in una coppia, infatti, introduce gradi di libertà aggiuntivi; questi gradi di libertà sono però vincolati. Un’opportuna modellazione delle coppie cinematiche affette da gioco permette di esprimere analiticamente per mezzo di opportune funzioni il vincolo sui gradi di libertà introdotti. E’ quindi possibile studiare la funzione che rappresenta l’errore di posizionamento del membro di riferimento riconducendo il problema alla massimizzazione di una funzione continua definita su un dominio compatto. La soluzione al problema è ottenuta analiticamente in forma chiusa, modellando coppie di tipo rotoidale, prismatico, cilindrico e sferico per meccanismi piani e spaziali.